Faktor-Faktor yang Mempengaruhi Time Theft pada Karyawan Excelso Jakarta dengan Work Passion sebagai Mediasi - Qusai, Adil; Putri, Marlina Melani; Sanger, Johan Frederick; Emilisa, Netania (Bisnis-Net, 2025)
This study examines the influence of perceived insider status and supervisor developmental feedback on employee time theft, with work passion as a mediating variable, among employees at Excelso café outlets in Jakarta. Amid increasing competition in the café and restaurant industry, unethical behaviors like time theft pose a threat to productivity and organizational efficiency. Using a quantitative cross-sectional approach, data were collected from 120 Excelso employees through purposive sampling and analyzed using SEM with SPSS and AMOS. The results show that perceived insider status and supervisor developmental feedback both have a significant positive effect on work passion. In turn, work passion significantly reduces the tendency for time theft. Additionally, both perceived insider status and supervisor developmental feedback show a significant negative impact on time theft, both directly and indirectly through work passion. These findings highlight the importance of fostering employee engagement and supportive feedback mechanisms to build emotional attachment to work, which ultimately minimizes unproductive behaviors. The study contributes to the literature by demonstrating the mediating role of work passion in reducing time theft in the food and